Prevalence of osteopathologies in a single center cohort of survivors of childhood primary brain tumor - Schündeln, Michael M.; Fritzemeier, Sebastian; Goretzki, Sarah C.; Hauffa, Pia K.; Munteanu, Martin; Kiewert, Cordula; Hauffa, Berthold P.; Fleischhack, Gudrun; Tippelt, Stephan; Grasemann, Corinna (Frontiers in Pediatrics, 2022)
Background: Childhood primary brain tumors (CPBT) are the second largest group of childhood malignancies and associated with a high risk for endocrine late effects. Objective: To assess endocrine late effects and their relevance for the development of osteopathologies in survivors. Methods: This single center cross sectional study investigated data from 102 CPBT survivors with a mean age of 13.0 years and a mean age at diagnosis of 8.7 years. Clinical, biochemical, radiographic and anamnestic data regarding endocrine and bone health were obtained at study visits. In addition, data regarding tumor stage and therapy was obtained by chart review. An expert opinion was applied to define presence of osteopathologies. Results: Impaired bone health, defined by at least one pathological screening parameter, was present in 65 % of patients. 27.5% were found to have overt osteopathologies per expert opinion. 37.8 % displayed a severe vitamin D deficiency (25-OH vitamin D < 10 ng/ml) and 11 % a secondary hyperparathyroidism. Patients with osteopathologies had lower 25-OH vitamin D levels compared to patients without osteopathologies. Multiple endocrine late effects were present: diabetes insipidus in 10.8 %, aberrant pubertal development in 13.7 %, central hypocortisolism in 14.9 %, thyroid dysfunction in 23.8 % and growth hormone deficiency in 21.8 %. A total of 31.3 % of survivors displayed any endocrinopathy. Tumors located near hypothalamic structures and patients who received irradiation had a higher likelihood of endocrine morbidity. Conclusion: This study indicates that endocrine deficiencies are common in pediatric survivors of CPBTs. Osteopathologies are present in this cohort. A prominent effect of hormonal deficiencies on bone health was not detected, possibly because patients were sufficiently treated for their endocrine conditions or indicating resilience of the childhood bone remodeling process. Vitamin D deficiency is frequent and should be treated as recommended.